2020
DOI: 10.1038/s41467-020-19897-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale imaging of bacterial infections by sphingolipid expansion microscopy

Abstract: Expansion microscopy (ExM) enables super-resolution imaging of proteins and nucleic acids on conventional microscopes. However, imaging of details of the organization of lipid bilayers by light microscopy remains challenging. We introduce an unnatural short-chain azide- and amino-modified sphingolipid ceramide, which upon incorporation into membranes can be labeled by click chemistry and linked into hydrogels, followed by 4× to 10× expansion. Confocal and structured illumination microscopy (SIM) enable imaging… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 54 publications
0
58
0
Order By: Relevance
“…PG thus poses a problem for ExM, since the original ExM protocols were developed for eukaryotic cells. Previously, it has been shown that PG has to be digested by lysozyme in order to enable isotropic expansion of bacteria in mixed communities ( Lim et al., 2019 ) or within host cells ( Gotz et al., 2020a ). In addition, MurNAc residues are modified by peptide chains that are cross-linked connecting individual PG layers ( Brott and Clarke, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PG thus poses a problem for ExM, since the original ExM protocols were developed for eukaryotic cells. Previously, it has been shown that PG has to be digested by lysozyme in order to enable isotropic expansion of bacteria in mixed communities ( Lim et al., 2019 ) or within host cells ( Gotz et al., 2020a ). In addition, MurNAc residues are modified by peptide chains that are cross-linked connecting individual PG layers ( Brott and Clarke, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…HeLa229 cells were seeded on 15 mm glass slides (VWR) in multiwell plates (Corning) one day prior to infection. Staining of S. negevensis was achieved by membrane staining according to ( Gotz et al., 2020a ). For immunostaining, the samples were washed in 1× PBS and fixed with 4% PFA in PBS (Morphisto) for 15 min at RT.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations